Análises estruturais da lectina de Canavalia maritima complexada com auxinas naturais e sintéticas - Sousa, Jucilene Pereira de (2022)
Auxins are a class of phytohormones that are included in a range of plant growth and development processes. These processes include cell division, cell growth, and cell differentiation, which underlie many types of organogenesis and growth responses. Natural auxins are composed of aromatic molecules with carboxylic acid moieties such as indole-3-acetic acid (IAA) and indole-3-butyric acid (IBA) and there are still some synthetic growth regulators with auxin-like activity such as 2,4-dichlorophenoxyacetic acid (2,4-D). Considering that legume lectins are also involved plant growth and development, the objective of this work was to characterize the interaction of Canavalia maritima (ConM) lectin with the phytohormones IBA and 2,4-D, which will completely describe the auxin binding site in these proteins. To achieve these goals, ConM lectin was co-crystallized with IBA and 2,4-D and solved at a 1.8 and 1.6 Å resolution, respectively. The site of interaction of ConM with the auxins is conserved, IBA formed hydrogen bond with Asn131 and established van der Waals interactions with Thr49 and 2,4-D formed hydrogen bonds with Thr49/Ser110 and van der waals interactions with Thr49/Asn131. Although IBA and 2,4-D bind at the same binding site in ConM compared to IAA in ConM and ConBr, their orientations are different. Comparing IAA complexed with ConM and ConBr, all bind to the amino acid residue Asn131. IAA complexes bind to amino acid residue Ser108. On the other hand, only 2,4-D is bound to residue Ser110. Additionally, all complexes were stabilized by van der Waals interactions or hydrogen bonds with Thr49, except ConM/IAA. It is also important to highlight that the positions of IBA and 2,4-D were very similar, however they differed briefly in relation to the type of bond, distance and amino acid residues involved. The high similarity between the sequences of Canavalia lectins allow us to affirm the conservation of the auxin binding site in this group of lectins. The difference between the interactions described in the work may be evidence of the different ability to modulate the concentrations of auxins available in the early stages of development, of the reciprocal action on the expression or synthesis of lectins and/or proteins related to the synthesis of auxins in the plant.